Slope constrained material design - Schury, Fabian; Stingl, Michael; Wein, Fabian (Structural and Multidisciplinary Optimization, 2012)
We investigate a class of constrained inverse homogenization problems. The complexity of the topological solution is restricted using slope constraint regularization. We show existence of the solution for the inverse optimization problem in function space and outline a converging approximation scheme. We demonstrate how a proper numerical implementation can lead to a stable material design approach. We finally describe results for a comprehensive set of numerical test cases.
Keywords: Slope constraints; Inverse homogenization; Topology optimization; SIMP